Marāṭhī bhāshecā vikāsa : Bibliotheque de l'ecole des hautes etudes (sciences hist. et phil) hyā mālentīla 211 vẽ pustaka La formation de la langue Marathe hyācā Marāṭhī anuvāda - Bloch, Jules, 1880-1953 (SAMP early 20th-century Indian books project, 1941)
History and development of Marathi language.